ISLAMIC RELIGIOSITY AND ISLAMIC BRANDING ON MSMEs PERFORMANCE: FINANCIAL KNOWLEDGE AS MEDIATION - Ferdy; Muhammad Ali Fikri (Islamic Economics Program, Faculty of Islamic Economics and Business, 2024)
This study aims to determine the effect of Islamic religiosity and Islamic Branding on Micro, Small and Medium Enterprises (MSMEs) performance mediated by Financial Knowledge. The purpose of this research is to enrich the literature and also to provide a strong foothold in developing entrepreneurial strategies with sharia principles and try to examine the factors to take advantage of this potential. This research is particularly interesting because currently, research on the role of Religion on entrepreneurship in Indonesia is limited and scarce, mostly conducted on Western and non-Muslim businesses. Currently, the Islamic economy and halal industry are growing rapidly in both local and global markets. However, the fact is that the potential of the Islamic economy has not been maximally utilized by entrepreneurship in Indonesia. Therefore, this research focuses on sharia management and Entrepreneurship with the aim of not only influencing consumer preferences, but also providing a strong foothold in developing products, services, and management strategies that are in accordance with sharia principles to capitalize on the potential of the sharia economy. This study used purposive sampling method to collect data, using a questionnaire with the criteria of Muslim entrepreneurship owners or managers in MSMEs. This study uses quantitative data processing methods using structural equation modeling partial least squares analysis with Smart PLS 4.0 statistical tools. Islamic religiosity directly affects the performance of organization and affects financial capability and Islamic branding affects financial knowledge but does not directly affect the performance of organization. In addition, organization performance is influenced by individual financial knowledge. Another finding is that financial knowledge mediates Islamic religiosity but has no effect for Islamic branding on organizational performance.